Pengaruh Interaksi Sosial Terhadap Kemandirian Belajar Siswa - Bayu Suci Nur Cahya; Yuyun Elizabeth; Nurlinda Safitri (STKIP Andi Matappa Pangkep, 2022)
Thesis of Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, Bogor, 2022. This research is a quantitative study through a causal approach, the purpose of the study is to determine the effect of social interaction on student learning independence. This research was conducted to test the validity of the instrument variables of social interaction and student learning independence using Pearson's Product Moment formula and reliability test using Cronbach's Alpha formula. The population in this study were students in grades III A and III B at SDN Kedung Waringin, Bogor City, for the academic year 2021/2022, totaling 60 students. The sample used was 37 students, which was obtained using the Taro Yamane formula. Furthermore, research data was taken and analyzed using the Normality, Homogeneity, and Linearity Test. The results of this study indicate that it can be shown from the regression equation = - 86.10+(1.87X). This means that every one unit increase in the Social Interaction variable will cause an increase in the Learning Independence variable of 1.87 units.